2015
DOI: 10.1002/cncr.29382
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on complementary/alternative medicine use among survivors of hematopoietic stem cell transplant: Benefits and uncertainties

Abstract: The widespread use of complementary and alternative medicine (CAM) in cancer survivors is well known despite a paucity of scientific evidence to support its use. The number of survivors of hematopoietic stem cell transplant (HCT) is growing rapidly and HCT clinicians are aware that many of their patients use CAM therapies consistently. However, due to a paucity of data regarding the benefits and harms of CAM therapies in these survivors, clinicians are reluctant to provide specific recommendations for or again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The most frequently tested interventions in randomized clinical trials include exercise (148, 157161), cognitive behavioral therapy (149, 152, 162), and mind-body practices with stress management (161, 163165). Multiple randomized trials of these interventions have shown small to moderate benefits in improving HRQOL, and reducing fatigue and psychological distress in HCT recipients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently tested interventions in randomized clinical trials include exercise (148, 157161), cognitive behavioral therapy (149, 152, 162), and mind-body practices with stress management (161, 163165). Multiple randomized trials of these interventions have shown small to moderate benefits in improving HRQOL, and reducing fatigue and psychological distress in HCT recipients.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple randomized trials of these interventions have shown small to moderate benefits in improving HRQOL, and reducing fatigue and psychological distress in HCT recipients. However, interventions vary substantially in intensity from self-directed programs to highly supervised one-on-one specialist involvement (148, 149, 157, 160, 163). Notably, higher-intensity interventions with substantial interventionist input yielded larger and more significant and enduring benefits (149, 163).…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that by increasing polypharmacy and the pill burden experienced by allogeneic HSCT survivors (a group already taking a large number of supportive care medications), CAM therapies may also increase the likelihood of nonadherence . Alternatively, several randomized controlled studies, particularly mind and body interventions were found to have potential benefits in this patient group . For example, Takatsuka et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that by increasing polypharmacy and the pill burden experienced by allogeneic HSCT survivors (a group already taking a large number of supportive care medications), CAM therapies may also increase the likelihood of nonadherence [18]. Alternatively, several randomized controlled studies, particularly mind and body interventions were found to have potential benefits in this patient group [9]. For example, Takatsuka et al demonstrated a beneficial effect of fish oil on the incidence of graft-versus-host disease (GVHD) in patients after HSCT [19] and two studies have found a significant positive correlation between massage therapy and a decline in anxiety and depression level in patients after HSCT [20,21].…”
mentioning
confidence: 99%
“…15 A case-control study reported that patients with cancer facing stem-cells transplant affirmed reduction of pain after relaxation sessions with music. 11 A Hawaiian integrative review and a American systematic review described reduction of pain during venous and lumbar puncture, respectively, in children with cancer. 18,19 A German systematic review and meta-analysis reported results of pain easing due to use of music still in the preoperative period.…”
Section: Easing Of Acute or Chronic Painmentioning
confidence: 99%